Moment Generating Function of Geometric Distribution/Formulation 1/Examples/Second Moment

From ProofWiki
Jump to navigation Jump to search

Examples of Use of Moment Generating Function of Geometric Distribution

Let $X \sim \Geometric p$ for some $0 < p < 1$, where $\Geometric p$ is the Geometric distribution.

$\map X \Omega = \set {0, 1, 2, \ldots} = \N$
$\map \Pr {X = k} = \paren {1 - p} p^k$


The second moment generating function of $X$ is given by:

$\map { {M_X}''} t = p \paren {1 - p} e^t \paren {\dfrac {1 + p e^t} {\paren {1 - p e^t}^3} }$


Proof

We have:

\(\ds \map { {M_X}''} t\) \(=\) \(\ds \frac \d {\d t} \map { {M_X}'} t\) Definition of Moment Generating Function
\(\ds \) \(=\) \(\ds \frac \d {\d t} \dfrac {p \paren {1 - p} e^t} {\paren {1 - p e^t}^2}\) First Moment
\(\ds \) \(=\) \(\ds p \paren {1 - p} \frac \d {\d t} \paren {e^t \paren {1 - p e^t}^{-2} }\) factoring out the $p \paren {1 - p}$
\(\ds \) \(=\) \(\ds p \paren {1 - p} \paren {e^t \paren {1 - p e^t}^{-2} + e^t \paren {-2 \paren {1 - p e^t}^{-3} } \paren {-p e^t} }\) Product Rule, Chain Rule for Derivatives, Derivative of Power, Derivative of Exponential Function
\(\ds \) \(=\) \(\ds p \paren {1 - p} \paren {\dfrac {e^t} {\paren {1 - p e^t}^2} \dfrac {\paren {1 - p e^t} } {\paren {1 - p e^t} } + \dfrac {2 p e^{2 t} } {\paren {1 - p e^t}^3} }\) multiplying by $1$
\(\ds \) \(=\) \(\ds p \paren {1 - p} e^t \paren {\dfrac {1 + p e^t} {\paren {1 - p e^t}^3} }\) simplifying

$\blacksquare$